2017
DOI: 10.7567/apex.11.011305
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence of superatom-like Ge-core/Si-shell quantum dots by alternate field-effect-induced carrier injection

Abstract: We have fabricated high-density superatom-like Si-Ge-based quantum dots (Si-QDs with Ge core) and studied their luminescence properties. Electroluminescence was observed from the Si-QDs with Ge core at room temperature in the near-infrared region by the application of squarewave pulsed bias of +1 V at 500 kHz, which was attributed to radiative recombination between quantized states in the Ge core with deep potential well for holes caused by field-effect-induced alternate electron/hole injection from the substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We have focused on CVD formation and characterization of Si-QDs with Ge-core, and reported room temperature photoluminescence (PL) properties attributable to type II energy-band alignment between the Ge-core and the Si-shell [10][11][12][13][14][15]. In addition, we have also demonstrated stable electroluminescence in the near-infrared region from light-emitting-devices having a 3-fold stacked Si-QDs with Ge core with an areal density of ~2.0×10 11 cm −2 under pulsed bias applications [16]. One of the possible ways to enhance the radiative recombination rate and improve the light emission efficiency is to reduce non-radiative centers and increase carrier density with impurity doping into the QDs.…”
Section: Introductionmentioning
confidence: 83%
“…We have focused on CVD formation and characterization of Si-QDs with Ge-core, and reported room temperature photoluminescence (PL) properties attributable to type II energy-band alignment between the Ge-core and the Si-shell [10][11][12][13][14][15]. In addition, we have also demonstrated stable electroluminescence in the near-infrared region from light-emitting-devices having a 3-fold stacked Si-QDs with Ge core with an areal density of ~2.0×10 11 cm −2 under pulsed bias applications [16]. One of the possible ways to enhance the radiative recombination rate and improve the light emission efficiency is to reduce non-radiative centers and increase carrier density with impurity doping into the QDs.…”
Section: Introductionmentioning
confidence: 83%
“…Si-based Ge quantum dots (Ge/Si QDs) exhibited many novel photoelectric properties due to their quantum confinement effect and compatibility with Si-based circuits, which have a potential in applying in optoelectronic devices, such as CMOS-compatible lasers, emission light source of on-chip optical interconnects, thermoelectric devices, QD solar cells, near infrared detectors and so on [1][2][3][4]. The morphology and structure of single-layer QDs was highly required for the future application; however, the part of physical character of multi-layer QDs was better than single-layer for using in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [27] demonstrated, adopting the potential morphing method and the effective mass approximation, a considerable enhancement of the nonlinear dielectric function and the refractive index (RIs) by increasing the shell thickness with and without impurity. Moreover, luminescent Ge/Si core/shell structure has been studied in [28], authors have grown the super atom-like Ge (core) in a Si shell. They investigated the luminescence properties and observed electroluminescence in the near infrared at room temperature (RT) concluding about radiative recombination mechanism involving field-effect-induced injection via substrate.…”
Section: Introductionmentioning
confidence: 99%